2015
DOI: 10.1016/j.jpowsour.2015.04.095
|View full text |Cite
|
Sign up to set email alerts
|

Impact of micro-porous layer on liquid water distribution at the catalyst layer interface and cell performance in a polymer electrolyte membrane fuel cell

Abstract: In polymer electrolyte membrane fuel cells, a gas diffusion layer (GDL) with a micro-porous layer (MPL) gives better anti-flooding performance than GDLs without an MPL. To investigate the function and mechanism of the MPL to suppress water flooding, the liquid water distribution at the cathode catalyst layer (CL) surface are observed by a freezing method; in the method liquid water is immobilized in ice form by rapid freezing, followed by disassembling the cell for observations. The ice covered area is quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 19 publications
(39 reference statements)
2
26
0
1
Order By: Relevance
“…This suggests that the MPL can prevent water accumulation in the flow field land area, where high contact pressure is observed; at the same time, however, at the decreased contact pressure in the channel regions, liquid water can accumulate in gaps between the MPL and the cathode electrode layer. 7,14,15,53 Finally, this is also supported by the calculation of the water storage capacities at the cathode/MPL interface based on surface roughness measurements: Swamy et al predict a three times higher maximum water content inside interfacial gaps without applied compression in the flow field channels compared to 1.5 MPa, which corresponds to a typical flow field land compression pressure. 14 The here presented effect of high oxygen mass transport resistances at very low compressions is not only relevant in case of inhomogeneous compression of the diffusion medium, e.g., if the cells of a stack are locally under compressed.…”
Section: F598mentioning
confidence: 71%
“…This suggests that the MPL can prevent water accumulation in the flow field land area, where high contact pressure is observed; at the same time, however, at the decreased contact pressure in the channel regions, liquid water can accumulate in gaps between the MPL and the cathode electrode layer. 7,14,15,53 Finally, this is also supported by the calculation of the water storage capacities at the cathode/MPL interface based on surface roughness measurements: Swamy et al predict a three times higher maximum water content inside interfacial gaps without applied compression in the flow field channels compared to 1.5 MPa, which corresponds to a typical flow field land compression pressure. 14 The here presented effect of high oxygen mass transport resistances at very low compressions is not only relevant in case of inhomogeneous compression of the diffusion medium, e.g., if the cells of a stack are locally under compressed.…”
Section: F598mentioning
confidence: 71%
“…The authors also observed the in-plane (direction parallel to the MEA surface) water distribution on the CL surface to understand the mechanism of the MPL suppression of water flooding. 19 The results indicated that water accumulation at the CL surface increases with increasing current density, and the addition of the MPL could suppress water accumulation at the CL surface as a result of the finer contact with the CL.…”
Section: F360mentioning
confidence: 90%
“…20 The authors also investigated the effect of the MPL/CL interface, and the results showed that an MEA made by the GDE method increases the cell voltage under wet conditions over those of an MEA made with the decal method at specific temperature conditions. 19 These results suggested that a smooth MPL/CL interface without gaps could be expected to prevent water accumulation and so improve cell performance.…”
Section: F360mentioning
confidence: 92%
“…It was shown that voids may be formed in CL, GDL or CL/MPL/ GDL interfaces under serious carbon corrosion conditions [52]. Liquid water may accumulate in such voids and delaminated locations and increase mass transport resistance [53]. During the recovery procedure, membrane and other components experience frequent swelling and contraction.…”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 99%